PEMANFAATAN KOLEKTOR SURYA SEBAGAI ENERGI ALTERNATIF DESALINASI AIR LAUT UNTUK MENGATASI KRISIS AIR BERSIH - Setiabudi, Dedet Hermawan; Khudhori, Muhrom (Sekolah Tinggi Teknologi Adisutjipto, 2015)
This research examined the effect of air velocity and the efficiency of double-pass flat plate solar air heater with two glass covers on the performance of solar desalination unit based on heat pump with using humidification and dehumidification processes. This unit consists of a heat pump, humidifier, dehumidifier, and double-pass flat plate solar air heater with two glass covers. The research was conducted in an indoor experiment. Solar energy generated from solar simulator using halogen lamps. In this research the air flow rate was varied at 3 metres per second, 4 metres per second, 5 metres per second, and 6 metres per second, while the intensity of solar radiation at 828 Watts per meter squared. At eachÂ variation in air velocity, sea water temperature was conditioned at a constant temperature of 45 degrees celcius, the compressor was operated at a constant rotation of 900 rpm, volumetric flow rate of sea water inlet 300 liters per hour into humidifier and sea water in this system was re-circulated. The research result showed that the volume of fresh water production increases with increasing air velocity inlet into humidifier. This solar desalination unit could produce fresh water maximum 2470 milliliters per hour in air velocity 6 metres per second.